(untitled) (European Bison Conservation Newsletter, 2013)
Presented is the list of papers and other publications released in 50 years after European bison reintroduction in Bieszczady. Analyzed was the subject of publication, as well as involvement of different scientific institutions. Together during those 50 year released were 103 publications. After analysis of this group of publications some conclusions came and between them some are more important. For sure needed is program of study of different aspects of wisent population, the health monitoring must be improved and universities from the region should be more involved in research. Also monitoring have to be coordinated.